Design and calibration of a new compound sensor for water content and electrical conductivity in soilless substrates. (January 2017) - Xu, Kun; Zhang, Xiliang; Chen, Shutian; Hou, Kun; Che, Yunfei
Reliable and affordable compound sensors for measuring the water content and electrical conductivity simultaneously in soilless substrates are limited. In this study, a new compound sensor based on dielectric theory and four-electrode method is presented, and the size of the sensor is determined with the help of ANSYS software. A water content calibration test is designed in vinegar residue and coconut chaff with the same electrical conductivity. Test results show that the water content calibration equation is suitable for different substrates. Similarly, an electrical conductivity calibration equation is obtained in different concentrations of salt solutions. Considering the influence of electrical conductivity to water content measurement, a two-factor (water content and electrical conductivity) orthogonal test is designed in coconut chaff. Based on the analysis of test results, two compensation models – the multiplicative model and the additive model – are proposed. To evaluate the reliability of the models, a multiple linear regression analysis is employed. The results indicate that the additive model has a relatively higher reliability, i.e. the additive model can be regarded as the compensation model. After compensation, the relative errors of the measured values (including volumetric water content and electrical conductivity) are no more than 10%, and the compound sensor is suitable for different soilless substrates without recalibration.